Contextual Bible reading and intercultural Bible reading: Four Colombian experiences - López, Edgar A. (HTS teologiese studies, 2021)
Contextual Bible Reading (CBR) and Intercultural Bible Reading (IBR) have enabled the cooperation between socially engaged scholars and marginalised groups to find new resources in biblical texts to interpret their contexts and fight against the surrounding violence. As the use of these two methods has not been the object of a comparative study based on concrete experiences, this article presents them through four cases of Christian communities in Colombia. This comparative study not only illustrates the differences between these two methods of Bible reading, but also shows how they open new hermeneutic and liberation perspectives in the struggle for social justice and the search for reconciliation. The article depicts the CBR of the story of the Levite’s concubine (Jdg 19:1–30) by a group of women living in vulnerable conditions as well as the CBR of the parable of the father and his two sons (Lk 15:11–32) by a group of violence victims’ relatives. It also depicts the IBR of the story of the widow and the judge (Lk 18:1–8) by four groups of Caribbean readers as well as the IBR of the garden story (Gn 2:4b–25) by two Andean indigenous groups. Ordinary readers’ central role as interpreters of biblical texts let them recognise their own capabilities to transform their contexts in an emancipatory way and challenge biblical scholars and theologians. Even though CBR and IBR pursue different hermeneutical goals, they converge in giving a central role to the community as the subject of counter-hegemonic interpretations that open new horizons starting from reality and triggering liberation processes.Contribution: Beyond their differences and tensions, CBR and IBR are inclusive and dialogical methods intended for liberation that should be used to transcend the limits of dominant interpretations of biblical texts as well as the isolation of marginalised ordinary readers.